Fuelling contempt for police: explaining why procedural injustice and police ineffectiveness damage Muslims’ trust in police - Ali, Mohammed M. (Policing and society, 2024)
Research shows that discriminatory policing can erode public trust in police. Yet, little research has examined the role that contempt can play in explaining this relationship. Focusing on Muslims in Australia, we test whether procedural justice and police effectiveness are associated with enhanced trust in police across two policing contexts (general duties policing and counterterrorism policing), and whether Muslims’ level of contempt for police mediates these relationships. Using survey data from 504 Muslims, we show that both procedural justice and police effectiveness are positively associated with Muslims’ trust in the police and negatively associated with contempt across both policing contexts. We also find that contempt is negatively associated with trust in both policing contexts. Finally, our findings show that contempt partially mediates the relationship between procedural justice and trust and between police effectiveness and trust. These findings reinforce the need for police to draw on procedurally fair and effective service delivery when engaging with minority groups who report strained relations with police. Our findings also highlight the need for scholars to closely consider distinct emotions as an important theoretical mechanism linking discriminatory police treatment with public (dis)trust of police.